Translation and Validation of Leicester Cough Questionnaire for Cystic Fibrosis Patients - Hadia Khan, Shoaib Waqas, Muhammad Tariq, Atiqa Niamat, Hafiz Muhammad Asim, Zeeshan Saeem (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To translate and validate Leicester cough questionnaire in Urdu language for patients with Cystic fibrosis. Methods: It is a cross-cultural linguistic study. 150 participants were included in the study and Non probability convenient sampling was used. Inclusion criteria includes parents of children with CF, who understand Urdu, and have symptoms of chronic cough. Children with severe respiratory exacerbations were excluded. Data was entered using SPSS version 25 and same software was used for data analysis. Results: It took 6 months to achieve an Urdu version of LCQ, which proved to be satisfactorily acceptable when administered to 150 subjects. The questionnaire showed acceptable internal consistency (Cronbach’s alpha =0.916), test-retest reliability by Pearson correlation ranged from 0.203 to 0.99 and intraclass correlation coefficient value 0.2 to 0.9 showed high reliability. Conclusion: Leicester Cough Questionnaire is a valid and reliable tool for assessing the impact of cough on quality of life in patients with Cystic fibrosis. Keywords: Cystic fibrosis, Cough, Health related quality of life, Leicester cough questionnaire.